Global epigenetic profiling identifies methylation subgroups associated with recurrence-free survival in meningioma - Olar, Adriana; Jones, David T. W.; Pfister, Stefan (Acta neuropathologica, 2017)
Meningioma is the most common primary brain tumor and carries a substantial risk of local recurrence. Methylation profiles of meningioma and their clinical implications are not well understood. We hypothesized that aggressive meningiomas have unique DNA methylation patterns that could be used to better stratify patient management.
Gesehen am 11.04.2018